2017
DOI: 10.1093/neuonc/nox176
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgery in molecularly defined low-grade glioma: an integrated clinical, radiological, and molecular analysis

Abstract: Our data provide the necessary reevaluation of the impact of surgery in molecularly defined LGG and support maximal resection as first-line treatment for molecularly defined LGG. Importantly, in IDH mutated astrocytoma, even small postoperative volumes have negative impact on OS, which argues for a second-look operation in this subtype to remove minor residues if safely possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
168
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(191 citation statements)
references
References 30 publications
7
168
2
Order By: Relevance
“…In addition, we observed that the EOR affected the survival outcome. As the treatment policy of our institution has been maximal safe surgical resection, the proportion of GTR was higher than that in other studies, which had a 4-15% GTR rates [12][13][14] . Consequently, we obtained relatively high survival rates in all three molecular subtypes as compared to those in other series.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In addition, we observed that the EOR affected the survival outcome. As the treatment policy of our institution has been maximal safe surgical resection, the proportion of GTR was higher than that in other studies, which had a 4-15% GTR rates [12][13][14] . Consequently, we obtained relatively high survival rates in all three molecular subtypes as compared to those in other series.…”
Section: Discussionmentioning
confidence: 57%
“…As grade II gliomas and grade III gliomas share molecular-genetic markers that are stronger prognostic factors than histologic grade, WHO grade II and III gliomas are now categorized together as "lower-grade gliomas". IDH-wildtype tumors are clinically similar to glioblastoma and are called as the glioblastoma-like subtype 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative genotyping matters for several reasons: in IDH mut astrocytoma even small residual volumes of tumour reduce survival (19), however, molecular results are not usually available during surgery. Glioblastoma therapy is considered appropriate for WHO II-III IDH wt gliomas, consisting of maximum safe resection followed by radiotherapy and chemotherapy.…”
Section: Single Slice Analysis For Idh Typingmentioning
confidence: 99%
“…There is thus a pressing need to identify new systemic therapies [9][10][11]. The variety in overall survival and response to treatment in GBM is largely due to the high heterogeneity of GBM with a different distribution of aggressive biological traits across tumors, as well as within a single tumor [12][13][14]. To classify GBM cases according to this heterogeneity, different prognostic factors have been suggested for GBM, including age, performance status, specific molecular markers [e.g., MGMT methylation (O 6 -methylguanine-DNA methyl-transferase), mutation of IDH1, IDH2(isocitrate dehydrogenase) or TERT (telomerase reverse transcriptase), 1p19q codeletion, overexpression of EGFR (epidermal growth factor receptor)], the size of necrosis and the extent of resection (EOR) [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%